Protease production by Pseudomonas aeruginosa isolates from patients with cystic fibrosis. - Hastie, A T (1983)
The temporal appearance of extracellular proteases produced by Pseudomonas aeruginosa was analyzed by pH 9 and pH 4 polyacrylamide gel electrophoresis (PAGE) and sodium dodecyl sulfate-PAGE. Ammonium sulfate precipitates of culture supernatants from various stages of growth revealed a time-dependent increase in number and amount of proteolytically active proteins. One mucoid P. aeruginosa clinical isolate and its derived nonmucoid variant, as well as two other nonmucoid variant P. aeruginosa strains (all from cystic fibrosis patients), showed similar production of five differently migrating proteases (P1 to P5, numbered according to increasing net negative charge) in pH 9 PAGE and one protease in pH 4 PAGE. P2, P3, and P5 increased to maximum concentrations at 24 to 48 h, decreasing thereafter, whereas P4 continued increasing even at 83 h, and P1 fluctuated. P3 was identified as an elastase. P2 was possibly composed of polypeptide chains bridged by disulfide bonds, since without reduction it migrated in sodium dodecyl sulfate-PAGE as a single protein, and with reduction it migrated as three protein bands. Two-dimensional PAGE revealed multiple molecular weight species within protease-positive bands in pH 9 gel strips. Isoelectric focusing gave a pattern of protein separation that correlated with two-dimensional PAGE analysis. Thus, greater heterogeneity of active proteases than previously reported has been demonstrated in all P. aeruginosa clinical isolates studied by sensitive two-dimensional PAGE analysis.